Rathke's cleft cyst associated with pituitary granulomatosis with polyangiitis: An unusual combination of hypothalamus-pituitary region pathologies - Riccardo Draghi, MD; Giovanna Mantovani, MD, PhD; Letterio Runza, MD; Giorgio Carrabba, MD; Nicola Fusco, MD; Paolo Rampini, MD; Antonella Costa, MD; Marco Locatelli, MD, PhD (Radiology Case Reports, 2018)
The authors present an unusual case of a patient suffering from visual deficit due to pituitary granulomatosis with polyangiitis (GPA) associated with Rathke's cleft cyst (RCC). The patient was referred to our Neurosurgery Department presenting right eye amaurosis, third cranial nerve palsy, and left temporal hemianopsia. Magnetic resonance imaging documented a sellar or suprasellar lesion with solid and cystic components. The dura mater of the skull base was also strongly enhanced. The patient underwent surgery. Histologic examination revealed RCC associated with pituitary GPA. To our knowledge, this is the first reported case of concomitant pituitary GPA and RCC. Pituitary involvement in GPA is rare, usually diagnosed in hormonal dysfunctions. The patient in case first presented optic chiasm compression, probably due to inflammation of both the pituitary gland and the previously asymptomatic RCC. We focus on the symptoms that led us to diagnose GPA pituitary involvement and on the peculiar and unusual Magnetic resonance imaging of the case presented.